E-Health Interventions for Adult and Aging Population With Intellectual Disability: A Review - Vázquez, Andrea; Jenaro, Cristina; Flores, Noelia; Bagnato, María José; Pérez, Ma Carmen; Cruz, Maribel (Frontiers in Psychology, 2018)
To answer the question about which e-health and e-therapy applications are being used with people with intellectual disabilities, we searched the PsycINFO, Medline, PubMed, ERIC, CINAHL, Scopus, Web of Science, and Cochrane databases. This is an extensive search. Inclusion criteria were academic journals and any design type that addressed the topic of interest. Studies that do not include adults or elderly, and studies that do not focus on people with disabilities but on third parties, were excluded. After an initial selection of 515 articles, 32 full-text articles were subjected to in-depth analysis leading to the final selection of 18 articles. We used the AAID framework definition of intellectual disability to analyze the dimensions explored by the selected studies and found that the majority of studies focused on the use of technology as supports to instrumental activities of daily life. The ISO classification of assistive products allowed us to identify that many e-health products are aimed at providing psychological or medical treatment. In summary, this review suggests that there is a very small number of studies focusing on the use of technology by older persons with intellectual disabilities. The studies present substantial limitations regarding generalization and replication and pay little attention to the maintenance of cognitive abilities in this population. These aspects, together with premature aging generally associated with many conditions that lead to intellectual disability, underscore the need to pay more attention to and develop e-health interventions for cognitive stimulation for this group.